Patterns of entrepreneurship management - Kaplan, Jack M.; McGourty, Jack (Hoboken, NJ, Wiley & Sons, 2020)
"Patterns of Entrepreneurship Management, 6th Edition is the essential roadmap for anyone interested in starting a new venture whether a for-profit or social enterprise. It is important to realize that entrepreneurship and company formation has changed radically in the last 2-3 years since our last edition. This text is totally new in this regard and provides the theory, cases, examples and tools for TODAY" S entrepreneurs. Students will be challenged with real situations and examples on which they can practice the broad range of skills required for lean startups and build a company in today's complex world. The over 40 worksheets currently developed act as prompts that help students focus on what should be considered at each stage of venture development. For each chapter, we will add specific content associated with each worksheet that will help the student understand the theory and/or rationale behind the prompts, helping the student connect the work with where they are in the venture process"--
Includes bibliographical references and index.
Keywords: Entrepreneurship